PERAN KELUARGA DALAM MENGATASI PERLAKUAN BULLYING PADA ANAK DI SMPN 3 KOTA JAMBI - Serli Rizki Novelia; Siti Amanah; Desy Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the role of the family in overcoming bullying in children, and how the parenting patterns of parents towards the child. This type of research is qualitative research with purposive sampling technique with the criteria of students at SMP N 03 Jambi City who are victims of bullying. The subjects consisted of 3 students. Data collection used interviews, observations, and documentation. The data was then reduced to be analyzed and conclusions drawn. From the results obtained, the role of parents in overcoming bullying in students was carried out at SMP N 03 Jambi City, namely in the form of providing good parenting patterns for children, creating good communication with children, providing advice and understanding about bullying in children, instilling social values ​​in children, and providing good examples and directions for children in everyday life.